Optical coherence tomography of outer retinal holes in senile retinoschisis and schisis-detachment. Issue 4 (24th June 2016) - Rachitskaya, Aleksandra V; Yuan, Alex; Singh, Rishi P; Sears, Jonathan E; Schachat, Andrew P
Abstract : Purpose: On clinical examination, it can be challenging to differentiate retinoschisis with outer retinal hole from schisis-detachment. This study examined the role of outer retinal hole spectral domain optical coherence tomography (SD-OCT) imaging in conjunction with imaging of the posterior schisis cavity edge in differentiating between these conditions. Methods: This is a retrospective case series. Out of 500 subjects with ICD-9 diagnoses of senile retinoschisis (361.10, 361.11, 361.12, 361.19) from January 2004 to December 2014, 62 had evidence of retinoschisis on fundus photography or optical coherence tomography (OCT). Six eyes of five patients had outer retinal holes documented by fundus photography (Optos, Marlborough, Massachusetts, USA) and SD-OCT (Carl Zeiss Meditec, Dublin, California, USA). The OCT morphology of outer retinal holes, subjects' symptomology, visual acuity, fundus examination, diagnosis and progression of the disease were analysed. Results: All five patients were women; the mean age was 67.4 years. The correct diagnosis was recorded in the chart in 50% of cases. All, but one, were asymptomatic with visual acuity ranging from 20/20 to 20/200. Three types of outer retinal hole OCT morphology in conjunction with imaging of the posterior schisis cavity edge were established. (1) Outer retinal hole with both edges down and attached to retinal pigment epithelium (RPE) and the edge of the cavity showing a split in neurosensory retina corresponded to isolated retinoschisis. The outer retinal hole with (2) one or (3) both edges detached from the RPE and the edge of the cavity showing complete separation of retina from RPE corresponded to schisis-detachment. One patient underwent scleral buckle surgery for schisis-detachment. Otherwise, no treatment was performed and no progression was noted with the longest OCT-documented follow-up of 26 months. Conclusions: The OCT morphology of outer retinal holes in conjunction with imaging of the posterior schisis cavity edge aids in the diagnosis of retinoschisis and schisis-detachment.